Pro-inflammatory interactions of streptolysin O toxin with human neutrophils in vitro - D. Joseph; A. J. Theron; C. Feldman; R. Anderson; G. R. Tintinger (Journal of Immunotoxicology)
The recent global resurgence of severe infections caused by the Group A streptococcus (GAS) pathogen, Streptococcus pyogenes, has focused attention on this microbial pathogen, which produces an array of virulence factors, such as the pore-forming toxin, streptolysin O (SOT). Importantly, the interactions of SOT with human neutrophils (PMN), are not well understood. The current study was designed to investigate the effects of pretreatment of isolated human PMN with purified SOT on several pro-inflammatory activities, including generation of reactive oxygen species (ROS), degranulation (elastase release), influx of extracellular calcium (Ca2+) and release of extracellular DNA (NETosis), using chemiluminescence, spectrophotometric and fluorimetric procedures, respectively. Exposure of PMN to SOT alone caused modest production of ROS and elastase release, while pretreatment with the toxin caused significant augmentation of chemoattractant (fMLP)-activated ROS generation and release of elastase by activated PMN. These effects of treatment of PMN with SOT were associated with both a marked and sustained elevation of cytosolic Ca2+concentrations and significant increases in the concentrations of extracellular DNA, indicative of NETosis. The current study has identified a potential role for SOT in augmenting the Ca2+-dependent pro-inflammatory interactions of PMN, which, if operative in a clinical setting, may contribute to hyper-activation of PMN and GAS-mediated tissue injury.